Pengaruh Kombinasi Neck Calliet Exercise dan Neuromuscular Taping terhadap Penurunan Nyeri Cervical Root Syndrome pada Penjahit di Sragen - Iim Alin Anjani; Dita Mirawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Cervical root syndrome (CRS) is a clinical condition caused by compression of the nerve roots in the neck area, often experienced by workers in static positions for long periods such a tailors. CRS can cause significant pain symtomps, affecting daily activities and quality of life. This study aims to determine the effect of a combination of neck calliet exercise and Neuromuscular taping on reducing pain in suffers of cervical root syndrome among tailors in Sragen. This research uses a design quasi-exsperimental with pre-test and post-test. the research subjectsw ere 26 tailor in sragen who where selected based on inclusion and exclusion criteria. The invertion provided is a combination of neck caliet exercise and Neuromuscular taping. pain levels were measured using NRS scale before and after the intervention. Before the intervention 76.9% of respondens experienced moderate pain (NRS score 4-6). while 23.1% experienced mild pain (NRS score 1-3). After the intervention 69.2% of respondents experienced in pain to the mild category, and only 30.8% still felt moderate pain. data analysis shows a significant reduction in pain levels after being given this combination intervention.The combination of neck calliet exercise and Neuromuscular taping is effective in reducing pain in sufferers of cervical root syndrome among tailors. this intervention can be an afficient pharmacological alternative treathment for chronic neck pain.